2019
DOI: 10.1101/820530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coordination of NDC80 and Ska complexes at the kinetochore-microtubule interface in human cells

Abstract: The conserved kinetochore-associated NDC80 complex (comprised of Hec1/Ndc80, Nuf2, Spc24, and Spc25) has well-documented roles in mitosis including (1) connecting mitotic chromosomes to spindle microtubules to establish force-transducing kinetochore-microtubule attachments, and (2) regulating the binding strength between kinetochores and microtubules such that correct attachments are stabilized and erroneous attachments are released. Although the NDC80 complex plays a central role in forming and regulating att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Interestingly, stable kinetochore-microtubule attachments formed earlier in these cells compared with cells expressing wild-type Hec1. However, consistent with a role for the tail domain in contributing to force generation at the kinetochore-microtubule interface, inter-kinetochore distances were decreased between sister kinetochores of bi-oriented chromosomes, and cells failed to silence the spindle assembly checkpoint (Wimbish et al, 2019). Based on these phenotypes, we hypothesize that attachments are established prematurely in early mitosis due to an inability to negatively regulate attachments by Aurora kinase-mediated phosphorylation; however, in later mitosis, the tail is required to provide an additional contact point to microtubules to achieve wild-type levels of force generation.…”
Section: Hec1 Tail Contribution To Kinetochore-microtubule Attachmentmentioning
confidence: 64%
See 4 more Smart Citations
“…Interestingly, stable kinetochore-microtubule attachments formed earlier in these cells compared with cells expressing wild-type Hec1. However, consistent with a role for the tail domain in contributing to force generation at the kinetochore-microtubule interface, inter-kinetochore distances were decreased between sister kinetochores of bi-oriented chromosomes, and cells failed to silence the spindle assembly checkpoint (Wimbish et al, 2019). Based on these phenotypes, we hypothesize that attachments are established prematurely in early mitosis due to an inability to negatively regulate attachments by Aurora kinase-mediated phosphorylation; however, in later mitosis, the tail is required to provide an additional contact point to microtubules to achieve wild-type levels of force generation.…”
Section: Hec1 Tail Contribution To Kinetochore-microtubule Attachmentmentioning
confidence: 64%
“…These results raise the possibility that the Ska complex may be able to, at least in part, compensate for the Hec1 tail domain in human cells. Indeed, a recent study from our lab demonstrated that HeLa cells depleted of Ska complex components and expressing a tail-less Hec1 mutant failed to establish stable kinetochore-microtubule attachments; however, this deficit could be restored when the Ska complex was left unperturbed (Wimbish et al, 2019). Thus, in a manner analogous to the coordinated activities of the NDC80 and Dam1 complexes in budding yeast (Kemmler et al, 2009;Demirel et al, 2012;Suzuki et al, 2016), the Ska complex likely functions in concert with the NDC80 complex in human cells in the establishment and maintenance of stable kinetochoremicrotubule attachments.…”
Section: Compensation For Hec1 Tail Function By Co-factorsmentioning
confidence: 97%
See 3 more Smart Citations